Dietary patterns drive loss of fiber-foraging species in the celiac disease patients gut microbiota compared to first-degree relatives - Roque, Ana (2024)
Background Celiac disease is an autoimmune disorder triggered by dietary gluten in genetically predisposed indi‑viduals that primarily afects the small intestine. Studies have reported diferentially abundant bacterial taxa in the gut microbiota of celiac patients compared with non-celiac controls. However, fndings across studies have inconsisten‑cies and no microbial signature of celiac disease has been defned so far. Results Here, we showed, by comparing celiac patients with their non-celiac 1st-degree relatives, that bacterial com‑munities of related individuals have similar species occurrence and abundance compared with non-relatives, regard‑less the disease status. We also found in celiac patients a loss of bacterial species associated with fber degradation,and host metabolic and immune modulation, as ruminiclostridia, ruminococci, Prevotella, and Akkermansia muciniphila species. We demonstrated that the diferential abundance of bacterial species correlates to diferent dietary pat‑terns observed between the two groups. For instance, Ruminiclostridium siraeum, Ruminococcus bicirculans, and Bacteroides plebeious, recognized as fber-degraders, appear more abundant in non-celiac 1st-degree relatives, which havea vegetable consumption pattern higher than celiac patients. Pattern of servings per day also suggests a possible link between these species’ abundance and daily calorie intake. Conclusions Overall, we evidenced that a kinship approach could be valuable in unveiling potential celiac disease microbial traits, as well as the signifcance of dietary factors in shaping microbial profles and their infuence on dis‑ease development and progression. Our results pave the way for designing and adopting novel dietary strategies based on gluten-free fber-enriched ingredients to improve disease management and patients’ quality of life.